ANALISIS QUANTITY TAKE OFF (QTO) PEKERJAAN STRUKTUR BERBASIS BUILDING INFORMATION MODELLING (BIM) PADA PROYEK KONSTRUKSI X - Nofriadi Nofriadi; Eka Juliafad; Harfa Sakri (LPPM Universitas Abdurrab, 2025)
Traditional QTO calculations are often performed manually based on 2D drawings, which are prone to errors, time-consuming, and difficult to integrate with other project processes. In response to these challenges, Building Information Modeling (BIM) has emerged as a transformative paradigm. BIM is a process that involves creating and managing intelligent 3D digital models of a building. BIM models contain not only geometric information but also rich non-geometric data, including material specifications, quantities, and relationships between elements. The use of BIM in the QTO process, known as 5D BIM, allows for automatic and accurate quantity extraction directly from the 3D model. Construction Project X is a 2-story reinforced concrete building construction project used as an office building. Construction Project X still uses conventional calculations in QTO planning, so researchers are trying to conduct further research related to BIM-based QTO planning in this construction project. The QTO modeling and analysis revealed relatively small differences in concrete elements and larger differences in reinforcement elements. Furthermore, in terms of cost, the BIM BOQ costed 10.26% more than the conventional QTO.